A male patient with atrial myxoma and multiple metastatic intracranial aneurysms: A case report and literature review - Min Xia; Yi Wang; Xuefeng An; Yufeng Huang; Ke Wei; Jia Zhou; Kun Li; Guojie Yao; He Huang (Journal of International Medical Research)
Atrial myxoma is the most common primary benign tumor of the heart, with over 75% occurring in the left atrium. The migration of myxoma cells can lead to rare neurological complications such as intracranial aneurysms, embolic strokes, and arteriovenous malformations. The most common neurological manifestations in such patients include seizures, nonspecific headaches, and cerebrovascular events. Herein, we present a rare case of a middle-aged man in his early 50s with metastatic myxomatous multiple fusiform aneurysms, who initially presented with the clinical manifestation of intracerebral hemorrhage. The patient underwent atrial myxoma resection, whereas the intracranial multiple fusiform aneurysms were managed conservatively. Four years later, digital subtraction angiography revealed progressive enlargement of the aneurysm in the A3 segment of the left anterior cerebral artery. We present the pathological report of the atrial myxoma and imaging findings showing the changes in the aneurysms, along with a review and summary of the relevant literature. This report offers new insights into treatment options for cases of atrial myxoma complicated with intracranial multiple aneurysms. This is the first reported case of a male patient in China presenting with intracerebral hemorrhage as the initial manifestation of atrial myxoma combined with multiple fusiform aneurysms.